Pengaruh Pemberian Reward dan Punishment Terhadap Disiplin Kerja Karyawan PT Valve Automation Indonesia - Arfita Widi Astuti; Yayat Sujatna (ITB Ahmad Dahlan Jakarta, 2020)
Good and skilled employee attitudes in the company can be created by applying rewards and punishments. The positive impact of employee discipline towards PT Valve Automation Indonesia is that the work produced can have a good impact on company income. The purpose of this study was to explain the effect of reward and punishment on employee work discipline, to analyze the effect of reward on employee work discipline, to analyze the effect of punishment on employee work discipline, and to analyze the magnitude of the effect of reward and punishment partially and simultaneously on employee work discipline at PT Valve Automation Indonesia. The research design used is descriptive, quantitative and associative methods, knowing the relationship between two or more variables, namely variable X1 (Reward) and variable X2 (Punishment) with symptoms or other variables, namely Y (Employee Work Discipline) at PT Valve Automation Indonesia. The data analysis method used in this study is multiple linear regression, analysis of multiple correlation coefficients, coefficient of determination, t-test and F test. Giving rewards and punishments for the work discipline of employees of PT Valve Automation Indonesia. Partially, there is a significant influence between reward and punishment with a significance value of 0.023 <0.05 and 0.013 <0.05 with a strong level of relationship based on the results of the correlation coefficient of 0.630 and 0.642. Simultaneously, there is a significant influence between reward and punishment on work discipline with a significance value of 0.000 <0.05 of 69.4%, the remaining 30.6% is influenced by other factors not in this study.